The Parable of the Disappearing Gladiators: Interpreting a Late Antique Cultural Reference in Genesis Rabba’s Exposition of the Cain and Abel Narrative - Williams, Benjamin (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2023)
According to the mashal (parable) attributed to Shimʿon ben Yoḥai in Gen. Rab. 22:9, the murder of Abel (Gen 4:8–10) may be likened to a gladiator’s death in the arena. This article argues that the parable assumes the audience’s familiarity with gladiatorial shows, which came to an end in the early fifth century CE. Tracing the transmission of the mashal in Tanḥuma ha-Nidpas (Bereshit 9) and the earliest commentaries on Genesis Rabba, it further argues that the gladiatorial allusion was not understood after the demise of the games, and that the Tanḥuma’s version is a later reformulation. The preservation of the imagery in the earliest extant manuscripts of Genesis Rabba, despite the fact that it was not well-understood when they were produced, demonstrates the conservation of a reference to a late antique public institution in medieval copies and thus contributes to the knowledge of Genesis Rabba’s textual history.